Alkaloid ligands enable function of homomeric human α10 nicotinic acetylcholine receptors - Hone, Arik J.; McIntosh, J. Michael (Frontiers in Pharmacology, 2022)
In the nervous system, nicotinic acetylcholine receptors (nAChRs) rapidly transduce a chemical signal into one that is electrical via ligand-gated ion flux through the central channel of the receptor. However, some nAChR subunits are expressed by non-excitable cells where signal transduction apparently occurs through non-ionic mechanisms. One such nAChR subunit, α10, is present in a discreet subset of immune cells and has been implicated in pathologies including cancer, neuropathic pain, and chronic inflammation. Longstanding convention holds that human α10 subunits require co-assembly with α9 subunits for function. Here we assessed whether cholinergic ligands can enable or uncover ionic functions from homomeric α10 nAChRs. Xenopus laevis oocytes expressing human α10 subunits were exposed to a panel of ligands and examined for receptor activation using voltage-clamp electrophysiology. Functional expression of human α10 nAChRs was achieved by exposing the oocytes to the alkaloids strychnine, brucine, or methyllycaconitine. Furthermore, acute exposure to the alkaloid ligands significantly enhanced ionic responses. Acetylcholine-gated currents mediated by α10 nAChRs were potently inhibited by the snake toxins α-bungarotoxin and α-cobratoxin but not by α-conotoxins that target α9 and α9α10 nAChRs. Our findings indicate that human α10 homomers are expressed in oocytes and exposure to certain ligands can enable ionic functions. To our knowledge, this is the first demonstration that human α10 subunits can assemble as functional homomeric nAChRs. These findings have potential implications for receptor regulatory-mechanisms and will enable structural, functional, and further pharmacological characterization of human α10 nAChRs.